An Edge-on Regular Disk Galaxy at z = 5.289 - Haojing Yan; Bangzheng Sun; Chenxiaoji Ling (The Astrophysical Journal, 2024)
While rotation-supported gas disks are known to exist as early as at z ≈ 7, it is still a general belief that stellar disks form late in the Universe. This picture is now being challenged by the observations from the James Webb Space Telescope (JWST), which have revealed a large number of disk-like galaxies that could be at z > 3, with some being candidates at z > 7. As an early formation of stellar disks will greatly impact our theory of galaxy formation and evolution, it is important to determine when such systems first emerged. Here we present D-CEERS-RUBIES-z5289 at z = 5.289 ± 0.001, the second confirmed stellar disk at z > 5, discovered using the archival JWST NIRCam imaging and NIRSpec spectroscopic data. This galaxy has a highly regular edge-on disk morphology, extends to ∼6.2 kpc along its major axis, and has an effective radius of ∼1.3–1.4 kpc. Such a large stellar disk is yet to be produced in numerical simulations. By analyzing its 10-band spectral energy distribution using four different tools, we find that it has a high stellar mass of 10 ^9.5–10.0 M _⊙ . Its age is in the range of 330–510 Myr, and it has a mild star formation rate of 10–30 M _⊙ yr ^−1 . While the current spectroscopic data do not allow the derivation of its rotation curve, the width of its H α line from the partial slit coverage on one side of the disk reaches ∼345 km s ^−1 , which suggests that it could have a significant contribution from rotation.